Absorption and Tensility of Bioactive Sutures Prepared for Cell Transplantation - Horváthy, Dénes B. (Materials (Basel), 2013)
Biodegradable scaffolds are widely used to transplant stem cells into various tissues. Recent studies showed that living stem cells can be attached to the surface of absorbable sutures in vitro. Soaking the absorbable material polyglactin in a cell culture medium and thereby creating a stem cell biofilm on its surface may initiate the absorption process even before implantation; therefore, the physicochemical properties of the suture may be compromised in vivo. We found that pre-incubation of sutures in cell culture media in vitro results in tensile strength reduction and faster suture absorption in a rat model of muscle injury. Shorter incubation times of up to 48 h do not influence absorption or tensility; therefore, it is advisable to limit incubation times to two days for polyglactin-based cell delivery protocols.